Advanced Circuit Design and Implementation of a Highly Digitalized Third-Order VCO-Based Sigma-Delta Modulator With Enhanced Noise Transfer Function - Shuenn-Yuh Lee; Yi-Ting Hsieh; Ju-Yi Chen (IEEE Access)
This study proposes an advanced circuit design to implement a highly digitalized current input third-order sigma-delta modulator (SDM) with enhanced noise transfer function (NTF). The proposed current input SDM can directly quantize current-type signals without any trans-impedance amplifier. Noise shaping with the proposed third-order SDM is realized via a passive integrator and two-stage voltage-controlled oscillator (VCO) phase integrators, which make the circuit structure highly digitalized and benefit from evolutionary fabrication techniques. The second VCO phase integrator can be easily realized by a current-steering digital-to-analog converter (I-DAC) because of the digital output from the previous phase integrator. This I-DAC is also used as the feedback path to develop current subtraction. A zero is implemented in the transfer function to establish the Chebyshev transfer function and further increase the resolution of the proposed SDM by the enhanced NTF. Measurement results reveal that the proposed highly digitalized SDM has a signal-to-noise and distortion ratio (SNDR) of 80.35 dB in the 10 kHz bandwidth and consumes $67.34~μ $ W under a supply voltage of 1.2 V, achieving a peak Schreier figure of merit (FoM) of 164.7 dB. The experimental setup of the proposed analog-front-end (AFE) architecture is also presented to showcase the AFE functionality.